Co-infection by Soil-Borne Fungal Pathogens Alters Disease Responses Among Diverse Alfalfa Varieties - Fang, Xiangling; Zhang, Caixia; Wang, Zi; Duan, Tingyu; Yu, Binhua; Jia, Xitao; Pang, Jiayin; Ma, Lisong; Wang, Yanrong; Nan, Zhibiao (Frontiers in Microbiology, 2021)
Fusarium oxysporum f. sp. medicaginis (Fom) and Rhizoctonia solani (Rs) are the major soil-borne fungal pathogens that pose severe threats to commercial alfalfa production in China. However, the effects of Fom and Rs co-infection on alfalfa and whether co-infection alters disease resistance responses among diverse varieties remain unknown. A collection of 80 alfalfa varieties (Medicago sativa) originated from seven countries were used to study the effects of Fom and Rs co-infection on alfalfa and host resistance responses. The co-infection resulted in more severe disease and reductions in growth and biomass allocation across varieties in comparison with either single infection by Fom or Rs; in addition, root morphology was much more strongly altered by the co-infection. Principal component analysis based on all plant traits showed that varieties under the co-infection were related to the single infection by Rs, being separated from Fom, and hierarchical clustering found differential response patterns among varieties upon co-infection compared with either single infection, with most varieties being highly susceptible to the co-infection. Furthermore, varieties that were most resistant to either single infection were not effective to co-infection, and there was no individual variety with resistance to both pathogens singly and co-infected. This study reveals for the first time that the co-infection by Fom and Rs alters disease resistance responses among diverse alfalfa varieties and provides useful information for developing alfalfa varieties with resistance to the co-occurrence of different soil-borne pathogens.